Effect of varieties/clones and fermentation time on the sensory quality of cup chocolate - Torres Segura, Darwin (2024)
In local cup chocolate production, the influence of cocoa varieties and fermentation conditions on its sensory characteristics are overlooked. The objective of the study was to sensorially evaluate chocolate made from two varieties and three clones of cocoa (Theobroma cacao L.) fermented for 5, 6, 7 and 8 days. Brix degrees and pH were recorded. Sensory evaluation was carried out with a panel of 10 judges. The research was experimental. Friedman's test and its multiple comparisons test were used. The maximum fermentation temperature reached was 51°C, decreasing to 38°C towards the end of the process. Both pH and initial brix degrees decreased from 4.6 to 4.15 and from 11 to 9.6, respectively. Differences were observed in the cocoa flavor and acidity attributes of Criollo cup chocolate at different fermentation periods. The 5-day fermentation was the one with the highest total score, followed by the UF-613 clone at 7 days, with 36 and 32 points, respectively. It is concluded that each variety/clone needs specific fermentation conditions, which influence sensory quality.   Keywords: Theobroma cacao, fermentation, sensory quality, varieties, clones